"Composing out": how gay and lesbian musicians use composing in their lives. Issue 1 (1st June 2016) - Antebi, Judy; Gilboa, Avi
Abstract : Background : The roles music plays in the "coming out" process have been scarcely studied, with less focus on gay and lesbian musicians who make a living from music. Objective : Present a qualitative research focusing on the roles that composing has for gay and lesbian musicians throughout their lives. Method : Eight participants with differing sexual identities, ages and backgrounds were interviewed. Participants were asked to describe personal "coming out" processes, within the context of their musical development, specifically as active composers. Discussion : Results are discussed in light of our profession as music therapists and in light of previous studies and models in the field of LGBTQ psychology. Conclusions : Analysis of the transcribed interviews revealed parallel processes between the "coming out" process of the interviewees and their developments as active composers and performers. Four key roles were identified: song as a therapist (maintaining secrets, regulating emotions, substituting therapists); song as a sensor (sharing feelings, checking out reactions of family and friends in a covert manner); song as a presenter (being an object through which to communicate and share sexual identity); song as a rebel (affecting audiences and protesting the "gay agenda" through concerts and albums).